Strategi Pelestarian Budaya Melalui Dokomentasi dan Publikasi - Dahlan, Mubarak (Rayhan Intermedia, 2024)
Culture is generally referred to as the ancestral heritage of a nation in a general context and in a specific context in a community that is considered as the heritage of the local community. Even the existence of culture is often considered as a characteristic of a community which is a distinguishing attribute between the local community and the community that is a member of another community. This paper examines the importance of the strategy of preserving Culture through documentation carried out by both the government and the general public at various age levels starting from the process of understanding the elements of Culture and the form of Culture. This type of research is a qualitative descriptive study that uses data from library sources in the form of books, scientific articles, popular scientific works, personal collection archives, government documents, and other types of sources. The results of the study indicate that the importance of preserving cultural values ​​through documentation and publication has so far become part of the Indonesian government program, among others, can be seen in efforts to identify elements that are part of the 10 objects of cultural advancement that have become national programs that are warmly welcomed in every region in Indonesia.